Research handbook on the law of professional football clubs / edited by Robby Houben. - Houben, Robby (Edward Elgar Publishing, 2023)
This handbook examines the key legal aspects of a professional football club's actions. Reflecting also on the role of key governing bodies such as UEFA, the handbook informs and contributes to the ongoing debate surrounding the governance and behaviours of professional football clubs.